P11 Barriers and facilitators to digital partner notification (PN) for sexually transmitted infections (STIs) and HIV: a systematic review and theoretical domains framework analysis. (16th June 2022) - Bloch, Sonja; McLeod, Julie; Flowers, Paul; Woodward, Charlotte; Lloyd, Karen; Gibbs, Jo; Estcourt, Claudia; Greevenbroek, Roos van; Owusu, Melvina Woode; Blandford, Ann; Mapp, Fiona; MacDonald, Jennifer; et al.
Abstract : Introduction: In an increasingly digitalised world where people seek and first contact sex partners online, digital interventions offer the potential to enhance PN for STIs and HIV. However, the ways in which they could improve PN outcomes are unknown. Methods: We conducted a systematic review of digital PN interventions for STIs/HIV in 8 databases to understand barriers and facilitators to such interventions. We used narrative synthesis to summarise the literature. We extracted barriers and facilitators for the behavioural foci: general notification (including but not differentiating between traditional and digital methods); digital notification (e.g., email, SMS, phone application); and partner management (sex partner testing/treatment). We then conducted a frequency analysis. Results: Eight studies fulfilled the inclusion criteria. They were heterogeneous in participants, digital interventions, and STIs/HIV considered. Unique to digital notification, barriers included problems with accessing technology. Facilitators included effective app functionality and apps enabling PN when contact details are unknown. These occurred alongside barriers and facilitators to notification in general, such as concerns about negative partner reactions and fear of shame (barriers) and social appropriateness of notification modality (e.g., email appropriate if face-to-face is not available) (facilitator). Discussion: Digital PN interventions are heterogenous and the differences are not clearly distinguished. Most interventions focus on notifying partners. Partner testing and treatment remains underexplored. There is a dearth of evidence on the barriers and facilitators to digital PN and further research is required. However, current evidence suggests that digital interventions can reduce some barriers to notification, but major barriers to PN in general endure. References: Balán, I. C., Rios, J. L., Lentz, C., Arumugam, S., Dolezal, C., Kutner, B., Rael, C. T., Ying, A. W., Macar, O. U., & Sia, S. K. (2022). Acceptability and Use of a Dual HIV/Syphilis Rapid Test and Accompanying Smartphone App to Facilitate Self- and Partner-Testing Among Cisgender Men and Transgender Women Who Have Sex with Men. AIDS and Behavior, 26 (1), 35–46. https://doi.org/10.1007/s10461-021-03322-9 Bilardi, J. E., Fairley, C. K., Hopkins, C. A., Hocking, J. S., Temple-Smith, M. J., Bowden, F. J., Russell, D. B., Pitts, M., Tomnay, J. E., Parker, R. M., Pavlin, N. L., & Chen, M. Y. (2010). Experiences and outcomes of partner notification among men and women recently diagnosed with chlamydia and their views on innovative resources aimed at improving notification rates. Sexually Transmitted Diseases, 37 (4), 253–258. https://doi.org/10.1097/OLQ.0b013e3181d012e0 Carnicer-Pont, D., Barbera-Gracia, M. J., Fernández-Dávila, P., García de Olalla, P., Muñoz, R., Jacques-Aviñó, C., Saladié-Martí, M. P., Gosch-Elcoso, M., Arellano Muñoz, E., & Casabona, J. (2015). Use of new technologies to notify possible contagion of sexually-transmitted infections among men. Gaceta Sanitaria, 29 (3), 190–197. https://doi.org/10.1016/j.gaceta.2015.01.003 Contesse, M. G., Fredericksen, R. J., Wohlfeiler, D., Hecht, J., Kachur, R., Strona, F. V., & Katz, D. A. (2019). Attitudes about the use of geosocial networking applications for HIV/STD partner notification: A qualitative study. AIDS Education and Prevention, 31 (3), 273–285. https://doi.org/10.1521/aeap.2019.31.3.273 Hopkins, C. A., Temple-Smith, M. J., Fairley, C. K., Pavlin, N. L., Tomnay, J. E., Parker, R. M., Bowden, F. J., Russell, D. B., Hocking, J. S., & Chen, M. Y. (2010). Telling partners about chlamydia: How acceptable are the new technologies? BMC Infectious Diseases, 10 (58). http://www.biomedcentral.com/1471-2334/10/58%5Cnhttp://ovidsp.ovid.com/ovidweb.cgi?T=JS&PAGE=reference&D=emed9&NEWS=N&AN=2010205630 Kutner, B. A., Pho, A. T., López-Rios, J., Lentz, C., Dolezal, C., & Balán, I. C. (2021). Attitudes and perceptions about disclosing HIV and syphilis results using Smarttest, a smartphone app dedicated to self-and partner testing. AIDS Education and Prevention, 33 (3), 234–248. https://doi.org/10.1521/aeap.2021.33.3.234 Lessard, D., Aslan, A., Zeggagh, J., Morel, S., Michels, D., & Lebouché, B. (2019). Acceptability of a digital patient notification and linkage-to-care tool for French PrEPers (WeFLASH©): Key stakeholders' perspectives. International Journal of STD and AIDS, 30 (14), 1397–1407. https://doi.org/10.1177/0956462419878043 Wang, A. L., Peng, R. R., Tucker, J. D., Chakraborty, H., Cohen, M. S., & Chen, X. S. (2016). Optimizing partner notification programs for men who have sex with men: Factorial survey results from South China. PLoS ONE, 11 (7), 1–14. https://doi.org/10.1371/journal.pone.0157749